Characteristics and outcome of warm autoimmune hemolytic anemia in adults: New insights based on a single‐center experience with 60 patients. Issue 9 (19th June 2014) - Roumier, Mathilde; Loustau, Valentine; Guillaud, Constance; Languille, Laetitia; Mahevas, Matthieu; Khellaf, Mehdi; Limal, Nicolas; Noizat‐Pirenne, France; Godeau, Bertrand; Michel, Marc
<x xml:space="preserve">Abstract</x> Warm autoimmune hemolytic anemia (wAIHA) is a rare autoimmune disease with poorly known natural history and management remaining mainly empirical. To better describe the characteristics and outcome of wAIHA in adults, we performed a single‐center cohort study of patients diagnosed with wAIIHA from 2001 to 2012 in our center. Sixty patients (50% women) were included, the mean age at the time of wAIHA onset was 54 ± 23 years. wAIHA was considered "primary" for 21 patients (35%) and was associated with an underlying disorder in 39 (65%), including mainly lymphoproliferative disorders and systemic lupus. All patients but two needed treatment and received corticosteroids, with an overall initial response rate of 87%. However, 63% of the patients were corticosteroid‐dependent and 56% required at least one second‐line treatment including mainly rituximab (n = 19). At the time of analysis, after a mean follow‐up of 46 months, 28 patients (47%) were in remission and off treatment and 5 (8%) had died. The presence of an underlying lymphoproliferative disorder was associated with reduced response to corticosteroids and increased need for second‐line therapy. In conclusion, in the last decade and compared to a previous series from our center, the rate of secondary wAIHA has increased and the use of rituximab has emerged as the preferred second‐line treatment and corticosteroid‐sparing strategy; the overall mortality has significantly decreased (8 vs. 18%). Am. J. Hematol. 89:E150–E155, 2014. © 2014 Wiley Periodicals, Inc.